On solution for the problem of spreading of acid water in canals - Dac, Nguyen Tat; Khu, Nguyen Phi (Vietnam Journal of Mechanics, 2000)
It is dealt within this study a one-dimensional mathematical and statistical model for acid water transport in canals including a case study in the Saigon river with data provided by Environment Protection Centre - HCM city. It is shown that based on statistical analysis of data collected in the field the computation will be improved in sense of making their solutions more reliable